PANDANGAN EMPAT TOKOH PEREMPUAN TERHADAP VIRGINITAS DALAM NOVEL GARIS PEREMPUAN KARYA SANIE B. KUNCORO: PERSPEKTIF FEMINIS RADIKAL - Ery Agus Kurnianto (Kantor Bahasa Sulawesi Tenggara, 2017)
In a patriarchal society, virginity is a symbol of personality for a woman. If a woman is able to keep herself virgin and serve it later to her husband after marriage, then she is valued as a “good” woman. On the other side, if a woman lost her virginity before marriage she will be labeled as “bad” woman. Furthermore how the opinions about virginity be seen through the four female characters glasses contained in the novel by Sanie B. Kuncoro? This article will discuss women’s point of view interpreted from four female characters in Garis Perempuan novel by Sanie B. Kuncoro. This research is a descriptive research. Therefore, this article is aimed to describe the different views of four female characters regarding virginity issue. Radical feminist theory is being applied to interpret the views of four female characters as identifying the character as the first step. The result shows that the virginity is a negotiable commodity to pull out women from the issue of life. Virginity is also seen as a dignity which is priceless. Virginity is a born treasure. Therefore, a woman has a right to give her virginity to whoever she wants without any interferences from patriarchal society.